Wireless edge caching modeling, analysis, and optimization - Baştuğ, Ejder 1985-; Chatzinotas, Symeon ca. 20./21. Jh; Quek, Tony Q. S. 1973- (Cambridge University Press, 2020)
Understand both uncoded and coded caching techniques in future wireless network design. Expert authors present new techniques that will help you to improve backhaul, load minimization, deployment cost reduction, security, energy efficiency and the quality of the user experience. Covering topics from high-level architectures to specific requirement-oriented caching design and analysis, including big-data enabled caching, caching in cloud-assisted 5G networks, and security, this is an essential resource for academic researchers, postgraduate students and engineers working in wireless communications